Characterization and simulation on antireflective coating of amorphous silicon oxide thin films with gradient refractive index. (August 2016) - Huang, Lu; Jin, Qi; Qu, Xingling; Jin, Jing; Jiang, Chaochao; Yang, Weiguang; Wang, Linjun; Shi, Weimin
Abstract: The optical reflective properties of silicon oxide (Six Oy ) thin films with gradient refractive index are studied both theoretically and experimentally. The thin films are widely used in photovoltaic as antireflective coatings (ARCs). An effective finite difference time domain (FDTD) model is built to find the optimized reflection spectra corresponding to structure of Six Oy ARCs with gradient refractive index. Based on the simulation analysis, it shows the variation of reflection spectra with gradient refractive index distribution. The gradient refractive index of Six Oy ARCs can be obtained in adjustment of SiH4 to N2 O ratio by plasma-enhanced chemical vapor deposition (PECVD) system. The optimized reflection spectra measured by UV–visible spectroscopy confirms to agree well with that simulated by FDTD method. Highlights: The Six Oy thin film is deposited on the substrate as antireflective coating by PECVD. Different reflection spectra with gradient refractive index are obtained by simulation. Reflection spectra with different structure are measured by UV–visible spectrometer. The characterization of reflective spectra verifies the modeling in FDTD simulation.